Deficient natural killer cell cytotoxicity in patients with IKK-γ/NEMO mutations - Orange, Jordan S. (American Society for Clinical Investigation, 2002)
NF-κB essential modifier (NEMO), also known as IKK-γ, is a member of the I-κB kinase complex responsible for phosphorylating I-κB, allowing the release and activation of NF-κB. Boys with an expressed NEMO mutation have an X-linked syndrome characterized by hypohidrotic ectodermal dysplasia with immune deficiency (HED-ID). The immunophenotype resulting from NEMO mutation is highly variable, with deficits in both T and B cell responses. We evaluated three patients with NEMO mutations (L153R, Q403X, and C417R) and HED-ID who had evidence of defective CD40 signaling. All three patients had normal percentages of peripheral blood NK cells, but impaired NK cell cytotoxic activity. This was not due to a generalized defect in cytotoxicity because antibody-dependent cellular cytotoxicity was intact. This abnormality was partially reversed by in vitro addition of IL-2, which was also able to induce NF-κB activation. In one patient with recurrent cytomegalovirus infections, administration of IL-2 partially corrected the NK cell killing deficit. These data suggest that NEMO participates in signaling pathways leading to NK cell cytotoxicity and that IL-2 can activate NF-κB and partially overcome the NK cell defect in patients with NEMO mutations.